EFL Students’ Needs in Promoting English Speaking Skills at Lower Secondary Schools - Israfil, Muhammad; Windy, Windy; Ningrum, Putri Kusuma; Apoko, Tri Wintolo (International Journal of Research in Education, 2024)
EFL Students’ needs for spoken English are considered important to fulfill, and the idea to capture what they need requires some ways and efforts so as to make them eager and keen on practicing English better. However, an analysis on needs environment is not much discussed and conducted for EFL students, mainly in lower secondary schools. Thus, the aim of this study is to examine the needs of EFL students in terms of enhancing their English-speaking skills in lower secondary schools. Three ninth-grade students from three distinct lower secondary schools located in Depok, West Java, Indonesia were the subjects of the research. This study employed a qualitative design with descriptive analysis, and the instrument used to collect the data was semi-structured interviews. The resulting data was analyzed with some steps such as reduction of data, data display, and data presentation. The results demonstrated that EFL students’ English-speaking proficiency is influenced by a variety of needs, including necessities, lacks, and wants. Considering the significance of these needs in the enhancement of EFL students' English-speaking abilities, it is advisable that teachers of English should comprehend and employ efficient learning strategies and stimulating learning media that facilitate the progress of students' English-speaking capabilities.